2008
DOI: 10.1002/apj.185
|View full text |Cite
|
Sign up to set email alerts
|

Electrical transport properties of aliovalent cation‐doped CeO2

Abstract: We report the comparative electrical properties of monovalent (Na + ), divalent (Ca 2+ , Sr 2+ ), trivalent (In 3+ , La 3+ ) and coupled substitution of divalent and trivalent (Ca 2+ + Sm 3+ ) cation-doped CeO 2 . The investigated samples were prepared by solid-state reaction (ceramic) using the corresponding metal oxides and salts in the temperature range 1000-1600 • C in air. Powder X-ray diffraction (PXRD), laser particle size analysis (LPSA), scanning electron microscopy (SEM), and ac impedance spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…Co-substituting two cation species is a promising approach for combining the positive effects of the substitution of single cations, that is beyond a mere additive effect. [18][19][20] Fig. S3 shows the oxygen ion diffusion behavior of the Gd 3+ /Ca 2+ , Nd 3+ /Ca 2+ and Lu 3+ /Ca 2+ co-substituted systems.…”
Section: Oxygen Ion Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-substituting two cation species is a promising approach for combining the positive effects of the substitution of single cations, that is beyond a mere additive effect. [18][19][20] Fig. S3 shows the oxygen ion diffusion behavior of the Gd 3+ /Ca 2+ , Nd 3+ /Ca 2+ and Lu 3+ /Ca 2+ co-substituted systems.…”
Section: Oxygen Ion Diffusionmentioning
confidence: 99%
“…Pearce and Thangadurai found that CeO 2 ceramics co-doped with rare-earth (La 3+ , Sm 3+ ) and alkaline earth ions (Ca 2+ , Sr 2+ ) exhibit higher ionic conductivities than those seen in singly-doped systems. 19 According to Xu et al, 20 the ionic conductivity of Ce 0.8+x Y 0.2-2x Ca x O 1.9 (x=0-0.1) at 700 °C initially increased and then decreased as the Ca 2+ concentration was increased further (34.2, 47.2 and 19.2 mS cm −1 for x=0, 0.05, and 0.1, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…We were able to optimize the bulk oxygen ion conductivity for Ce 0.85 Ca 0.05 Sm 0.1 O 1.9 in air (CCS) at 5.4×10 −3 S/cm at 700°C, which is comparable to that of YSZ [23]. The current study investigates the chemical compatibility of the CCS oxide ion electrolyte in air between 700 and 800°C with the IT-SOFC cathode material, SSC, and compares its electrochemical properties with that of conventional LSM cathodes.…”
Section: Introductionmentioning
confidence: 99%
“…In fact ceria is remarkably accommodating in terms of the substituent species that can be taken up and elements from all parts of the Periodic Table have been reported as substituting for cerium in its structure. 15 This includes transition-metals such as Fe 16 and Ti 17 , s-block cations, such as Ca 18 and Na 19 and main-group elements such as In 20 and Pb. 21 Each substituent element brings its own coordination preference and distinctive chemistry to the material that may be beneficial for catalytic applications.…”
Section: Introductionmentioning
confidence: 99%